ANALISIS PROFITABILITAS PADA PT. DUTA PERTIWI NUSANTARA - Rifal Dwi Putra; Tegar Zaki Hanafi; Taufiq Akbar Dewi Fidrdaus; Ratih Kusumastuti (CV. ALIM'SPUBLISHING, 2023)
This research was conducted to collect information about financial statements from 2021-2022, namely the balance sheet and income statement at PT Duta Pertiwi Nusantara. This study uses a theoretical basis from financial management theory regarding profitability ratio analysis of financial statements, the analytical tools used in this study are Gross Profit Margin, Net Profit Margin, Return on Investment and return on Equity. Based on the results of the analysis, it shows that the Gross Profit Margin of PT Duta Pertiwi Nusantara has decreased from 2021-2022, seen from the Net Profit and Return on Equity Margin during 2021-2022 the results show the same percentage, which has decreased in 2022. Then the Return On Investment achieved during 2021 to 2022 experienced a slight increase in 2022. The results of this study indicate that the profitability ratios in the financial statements of PT Duta Pertiwi Nusantara have not been stable and Based on the problem formulation of this study, namely